Dependence of Biofuel Ignition Chemistry on OH-Initiated Branching Fractions - Hartness, Samuel W.; Rotavera, Brandon (Frontiers in Mechanical Engineering, 2021)
Abstraction of hydrogen by ȮH is the dominant initiation step in low-temperature oxidation of biofuels. Theoretical chemical kinetics calculations for such reactions provide a direct means of quantifying rates of abstraction, which are critical to modeling biofuel combustion. However, in several cases and despite agreement on total rate coefficients, branching fractions (i.e. the distribution of initial radicals) can vary depending on the level of theory, which leads to variations in ignition delay time predictions. To examine the connection between branching fractions and ignition delay time predictions, simulations were conducted for 1-butanol, cyclopentanone, and methyl propanoate at 10 atm and from 500 – 1000 K. For each case, the simulations utilized recent combustion mechanisms to produce an initial set of ignition delay time trends. H-abstraction rates were then replaced using rates from the literature to examine the effects of ȮH-initiated branching fractions on ignition chemistry. Branching fractions were found to significantly influence ignition chemistry, specifically in the case of 1-butanol, even when total rate coefficients were relatively consistent. From comparison of site-specific rates in the literature, branching fractions for initiation of 1-butanol and methyl propanoate are not consistent, which resulted in ignition delay times differing by factors of up to 6.3 and 1.2 respectively. Conversely, in the case of cyclopentanone, for which both the total and the site-specific rate coefficients agree, ignition delay times were unaffected. From the observed dependence of ignition delay times on ȮH-initiated branching fractions, an intermediate step in the development of combustion mechanisms is necessary to validate site-specific rate coefficients and ensure accurate model predictions. Speciation measurements are one example that can provide a critical link to radical-specific, fundamental chemical pathways and determine accurate branching fractions .